2008
DOI: 10.1007/s00520-008-0451-z
|View full text |Cite
|
Sign up to set email alerts
|

Opioid-taking self-efficacy amongst Taiwanese outpatients with cancer

Abstract: The results of this study suggest it is important to understand how patients perceive their ability to perform key tasks associated with effective opioid-taking, to effectively tailor educational and supportive interventions. Patients with lower levels of education and with side effects of opioids may be at risk of lower self-efficacy, requiring particular attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Concerns about side effects and addictions were also reported as barriers of using opioids (Pang et al, 2013). In contrast, the patients’ belief that medications could be effective in treating pain (Lai et al, 2002) and high self-efficacy for administering opioids (Liang et al, 2008a, 2008b, 2012) were indicators of high adherence to opioids for cancer pain treatment.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Concerns about side effects and addictions were also reported as barriers of using opioids (Pang et al, 2013). In contrast, the patients’ belief that medications could be effective in treating pain (Lai et al, 2002) and high self-efficacy for administering opioids (Liang et al, 2008a, 2008b, 2012) were indicators of high adherence to opioids for cancer pain treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies reported using the WHO three-step ladder to guide the prescription of analgesics (Chen et al, 2007;Hu et al, 2010;Lu et al, 2006). Six studies specifically investigated the barriers of using opioids (Lai et al, 2002(Lai et al, , 2004Liang et al, 2008aLiang et al, , 2008bLiang et al, , 2012Liang et al, , 2013aLiang et al, , 2013bLiang et al, , 2015Pang et al, 2013), whereas the remaining 13 studies explored participants' perspectives on using analgesics.…”
Section: Prevalence Of Pain Type Of Pain Management and Adherence Bmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, previous studies in patients with cancer focused on self‐efficacy for physical activity showed that fatigue is a factor which lowered self‐efficacy for physical activity in patients with breast cancer and prostate cancer . Another study identified that education levels and side effects from opioids were related to lower levels of self‐efficacy in taking opioid analgesics for cancer patients in pain .…”
Section: Introductionmentioning
confidence: 99%